(untitled) (Journal of the Sociology and Theory of Religion, 2019)
From past centuries go back some religious demonstrations of the Catholic faithful. The brigantine processional traditions present themselves as public manifestations, in a junction and mixture of symbologies in the same ceremonial, accompanied by lay and religious entities, who assume in this participation an integrating and respectful link of these values ​​and of these beliefs, assuming the procession, also, as a social congregator. The representative iconographies of these popular devotions, in which the symbolic language adopted mirrors this respect and an unquestionable solemnity, reflect both aesthetic and artistic (re)interpretations. Identifying different glances that examine all these representative symbols integrated into subjective readings and apprehensions in an expression of devotional feelings.